Фазові рівноваги в системі Tl4P2Se6 – TlSbP2Se6 - Cабов Віктор; Victor Sabov; Поторій Марія; Potorij Mariia; П'ясецкі Міхал; Michal Piasecki; Федорчук Анатолій; Anatolii Fedorchuk; Філеп Михайло; Filep Mykhailo; Filep Mihály; Погодін Артем; et al. (ДВНЗ Ужгородський національний університет, 2020)
Резюме. Сполуки типу M2P2X6 на основі халькогенгіпофосфатів (де M – Mn, Fe, Co, Ni, Cd, V, Mg, Pb, Hg, Sn; X – S, Se), характеризуються різноманітними фізичними (сегнето-, п'єзо-, піроелектричні, термоелектричні, тощо) властивостями, що робить їх потенційно цікавими об’єктами оптоелектроніки, напівпровідникової техніки в цілому [1]. Спільним для них є [P2Se6] 4– структурний мотив, а також шарувата 2D структура. Наявність її стимулювало в останні рік-два дослідження халькогенгіподифосфатів у якості робочих елементів для спінтроніки [2]. Слід відмітити, що до сімейства халькогенгіподифосфатів окрім тернарних, належать тетрарні фази загальної формули M(I)M(III)P2S6(Se6), з тими самими структурним особливостями, що у тернарних. Враховуючи більшу варіативність по складу тетрарних представників слід також очікувати у них більш широкий спектр цікавих фізичних властивостей.

Abstract. Analysis of the literature and previous studies of the authors showed that the section Tl4P2Se6 - TlSbP2Se6 is quasi-binary, and given the closeness of the structures of the ternary and quaternary phases, there was a probability of mutual solubility of the initial components. All syntheses were carried out in vacuumed up to 0.13 Pa quartz ampoules. The synthesis of the samples in the system was carried out from the previously synthesized Tl4P2Se6 and TlSbP2Se6 at 850 K (48 hours). Annealing was carried out at 573 K (240 h), followed by quenching into ice water. The starting components were synthesized from pre-synthesized Tl2Se and elemental components taken in stoichiometric ratios. 11 samples were synthesized within the system (10 and 5 mol% at the starting compounds).The obtained samples were investigated by DTA methods (vacuum quartz vessels, chromel-aluminum thermocouple, heating rate 6°C/min) and XRD (DRON 4, Cu Kα radiation). On the diffraction patterns of the samples obtained, two reflex systems corresponding to the original compounds were observed. The Tl4P2Se6 – TlSbP2Se6 phase diagram is based on the DTA and XRD results with areas of solubility less than 5 mol% based on the initial components. Three polymorphic modifications of Tl4P2Se6 cause four lines of primary crystallization: three based on low-temperature (α-phase), medium-temperature (α / -phase) and high-temperature (α // - phase) modifications of Tl4P2Se6, as well as TlSbP2Se6. The eutectic process temperature (678 K) is lower than the polymorphic transformation temperature. The lines of the primary crystallizations of the α and β phases intersect at the non-variant eutectic point with the coordinates: 678 K, 55 mol% TlSbP2Se6. Metatectical processes involving high-temperature (α // - phase) and medium-temperature (α / - phase) modifications of Tl4P2Se6 are realized at temperatures of 746 K (α // ↔L + α / ) and 708 K (α / ↔L + α).
Phase equilibria in the Tl4P2Se6 - TlSbP2Se6 system
Keywords: діаграма стану; фазові рівноваги